NILAI AKUMULASI ANUITAS BERJANGKA DENGAN ASUMSI CONSTANT FORCE PADA STATUS HIDUP GABUNGAN - Desrinaldo '; Hasriati '; Rolan Pane (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
This article discusses the accumulated value of the immediate annuity by assuming constant force for m-times payment per year of two persons who are x  and y years old in joining term life insurance with joint life status. The constant force assumption isused in determining the accumulated value of the term immediate annuity. The accumulated value of the annuity is influenced by cash value annuity paid by the insurance participants, the interest rate, and the amount of annuity payments made by insurance participants.